0
$\begingroup$

In the derivation of the Ising model at zero field $B=0$, I stumbled upon a factor two in the textbook derivation that I don't understand.

We consider a 1D system of interacting spins $s_i$, where $i$ refers to the lattice site. Each spin pair $(s_i,s_{i+1})$ contributes an interaction energy $-Js_is_{i+1}$ to the system. To obtain the partition function we sum over all possible spin configurations $s:=(s_1,s_2,s_3,\ldots,s_N)$.

To achieve this, we apply a coordinate transformation $$s_1 \mapsto p_1,\\ s_1s_2 \mapsto p_2,\\ s_2s_3 \mapsto p_3,\\ \vdots\\ s_{N-1}s_N \mapsto p_N.$$

Our partition functions is now given by

$$ Z = \sum_s e^{-\beta J\sum_{i=1}^N s_is_{i+1}}\\ = \sum_s e^{-\beta J\sum_{i=2}^N p_i}\\ = \sum_s \prod_{i=2}^N e^{-\beta Jp_i}\\ = \color{red}{2}\prod_{i=2}^N\sum_{p_i=\pm 1} e^{-\beta J p_i} \\ =2(\color{red}{2} \cosh(-\beta J))^{N-1}. $$

I don't see where the $\color{red}{2}$ originates from.

$\endgroup$
2
$\begingroup$

The factor comes from the substitution of the sum in $s$ with the sum in $p$. Indeed, for every value of $p$ you have 2 different configurations in $s$ giving that result:

$$(s_i, s_{i+1}) = (+1,+1) \mapsto +1 $$ $$(s_i, s_{i+1}) = (+1,-1) \mapsto -1 $$ $$(s_i, s_{i+1}) = (-1,+1) \mapsto -1 $$ $$(s_i, s_{i+1}) = (-1,-1) \mapsto +1 $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.